Deception and truth detection when analyzing nonverbal and verbal cues - Vrij, Aldert (Applied cognitive psychology, 2019)
Summary In this article, I present my view on the significant developments and theoretical/empirical tipping points in nonverbal and verbal deception and lie detection from the last 30 years and on prospects for future research in this domain. I discuss three major shifts in deception detection research: (a) From observing target persons' nonverbal behavior to analyzing their speech; (b) from lie detection based on differences between truth tellers and liars' levels of arousal to lie detection based on the different cognitive processes or strategies adopted to appear convincing; and (c) from passively observing target persons to actively interviewing them to elicit or enhance verbal cues to deceit. Finally, I discuss my ideas for future research, focusing on initiatives from my own lab. Hopefully, this will stimulate other researchers to explore innovative ideas in the verbal deception research domain, which already has seen so much progress in the last decade.